THROUGHPUT CAPACITY OF HYBRID WIRELESS NETWORKS IS EXAMINED. - Жуков., І. А; Дворська, Л. О. (Science-based technologies, 2009)
Throughput capacity of hybrid wireless networks is examined. It has been shown that the capacity of a random ad hoc network does not scale well with the number of nodes in the system. Two different routing strategies and study the scaling behavior of the throughput capacity of a hybrid network are considered. Analytical expressions of the throughput capacity are obtained.